Plasmid segregation: how to survive as an extra piece of DNA. - Salje, J (2010)
Non-essential extra-chromosomal DNA elements such as plasmids are responsible for their own propagation in dividing host cells, and one means to ensure this is to carry a miniature active segregation system reminiscent of the mitotic spindle. Plasmids that are maintained at low numbers in prokaryotic cells have developed a range of such active partitioning systems, which are characterized by an impressive simplicity and efficiency and which are united by the use of dynamic, nucleotide-driven filaments to separate and position DNA molecules. A comparison of different plasmid segregation systems reveals (i) how unrelated filament-forming and DNA-binding proteins have been adopted and modified to create a range of simple DNA segregating complexes and (ii) how subtle changes in the few components of these DNA segregation machines has led to a remarkable diversity in the molecular mechanisms of closely related segregation systems. Here, our current understanding of plasmid segregation systems is reviewed and compared with other DNA segregation systems, and this is extended by a discussion of basic principles of plasmid segregation systems, evolutionary implications and the relationship between an autonomous DNA element and its host cell.